Prototype Management of Village Nurses and Telehealth for Improving Basic Healthcare Services in 3T Regions - Feninlambir, Renghart; Hasanbasri, Mubasyir (BKM Public Health and Community Medicine, 2024)
Purpose: The health issues in the 3T regions (Remote, Frontier, and Outer) are complex and require serious attention from the government and society. The 3T regions face challenges in accessing high-quality healthcare services due to healthcare personnel, access, resources, network, transportation, and information limitations. The shortage of healthcare personnel in the 3T regions is a significant issue, with the number of available healthcare personnel not matching the area's size and population. Efforts have been made to improve the public's access to high-quality healthcare services in the 3T regions. Still, the shortage of medical personnel and healthcare services remains a complex issue requiring more effective solutions. This prototype aims to develop an integrated village healthcare management system using telehealth technology to improve basic healthcare services in the 3T regions. This system should enable village nurses to monitor remotely, provide more effective services, and improve patient quality of life. Methods: This study uses a descriptive approach to outline the structure and components of the proposed program, referencing Mintzberg's organizational model. Results: The proposed program forms a structured organizational framework involving key stakeholders such as regional leaders, village heads, community health centers (Puskesmas), telemedicine services, and village-based nurses. Telemedicine is crucial, facilitating direct consultations between nurses and doctors, remote patient monitoring, patient education, and referrals to specialists. This integrated approach aims to improve healthcare accessibility, reduce geographical barriers, and strengthen collaboration among healthcare service providers. Conclusion: Implementing the "One Village, One Nurse, and Telemedicine" program is a strategic initiative to address the challenges of healthcare service provision in the remote 3T regions. This program aims to improve the availability and quality of basic healthcare services at the village level by establishing a structured organizational framework and utilizing telemedicine technology. This holistic approach has the potential to positively impact the health outcomes of people living in remote areas.